Efficacy of denosumab in joint preservation for patients with giant cell tumour of the bone. (May 2016) - Traub, Frank; Singh, Janith; Dickson, Brendan C.; Leung, Stephanie; Mohankumar, Rakesh; Blackstein, Martin E.; Razak, Albiruni R.; Griffin, Anthony M.; Ferguson, Peter C.; Wunder, Jay S.
Abstract: Background: Giant cell tumour of the bone (GCTB) is an aggressive osteolytic primary tumour. GCTB is rich in osteoclast-like giant cells and contains mononuclear cells that express RANK ligand (RANKL), a key mediator of osteoclast activation. The potential therapeutic effect of denosumab was investigated with special reference to its role in joint preservation. Methods: In this prospective non-randomised study patients with GCTB received denosumab for 6–11 months preoperatively. Serial radiographs and biopsy and resection tumour specimens were used to monitor response to denosumab. Results: All 20 patients experienced pain relief in the first month of treatment. All patients demonstrated a positive radiographic response with improved subchondral and cortical bone which allowed intralesional tumour resection and preservation of the joint and articular surface in 18 cases. Histological examination following denosumab revealed rarely detectable osteoclast-like giant cells. There was an obvious increase in osteoid matrix and woven bone which showed rare RANK staining amongst the mononuclear cells and only focal RANKL positivity. At median 30 months follow-up after resection, local tumour recurrence occurred in three patients. Conclusion: Denosumab provides favourable and consistent clinical, radiographic and pathologic responses which facilitates less aggressive surgical treatment, especially joint preservation. However, the local recurrence rate for GCTB following resection does not seem to be affected by denosumab and remains a concern. Highlights: Denosumab appears to be a useful adjuvant in the treatment of patients with giant cell tumour of the bone (GCTB). Denosumab provides favourable clinical, radiographic and pathologic responses. Using denosumab a higher rate of joint preservation is possible. Local recurrence rate of GCTB does not seem to be affected by denosumab.